(untitled) (KULT_online, 2017)
Here/There: Telepresence, Touch and Art at the Interface by Kris Paulsen critically examines telecommunication technologies that allow real-time interactions between remote subjects and areas. Discussing the works of seminal performance, video, and new media artists that experiment with telepresence technologies, Paulsen exposes the contradictory states of being that inhere the use of their interfaces, and how asymmetrical movements of power and agency are produced within them. In doing so, the book offers novel perspectives from which to discuss the ever-increasing interactions between the tangible world and the “physics of screens”.